Motion characteristics affect evaluation by judges in hip-hop dance: Kinematic analysis of step movement - Sato, N.; Nunome, H.; Ikegami, Y. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to extract motion characteristics closely related to high evaluation by judges, through a comparison of "side-step" movement between eight expert and eight non-expert dancers. Their step motions were captured and the head trajectory relative to the centre of mass, face inclination, and time lags among neck, trunk, hip and knee angles were calculated. As a result, a quarter cycle of phase delay between the neck motion and other body parts were observed for the expert dancers. This delay resulted in a large displacement of the head relative to the centre of mass and a large range of motion of the face inclination. The face inclination was highly correlated with the judging score (r = 0.869). Thus, it is assumed these motion characteristics are the most important element of the side-step movement that induces a better impression of judges.